2011
DOI: 10.1530/joe-10-0340
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone ameliorates diabetic nephropathy in a mouse model of type II diabetes

Abstract: Conventional therapies for diabetic patients, such as strict glycemic control, do not completely stop the progression of diabetic nephropathy. Serum-free tri-iodothyronine (T 3 ) levels were lower in patients with type II diabetes. The purpose of this study was to test a hypothesis that treatment with T 3 would improve diabetic nephropathy in db/db mice, a model of type II diabetes. Male db/db mice (16 weeks) were treated with T 3 for 4 weeks. Urinary excretions of albumin and blood glucose levels were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…And thyroid hormones can affect insulin signalling indirectly through affecting tyrosine phosphorylation of insulin receptor substrate and activation of phosphoinositide 3‐ kinase, serum FT3 levels are associated with insulin secretion . Furthermore, thyroid hormones and thyroid hormone receptors may play important roles in modulating the inflammatory response, and interactions have been demonstrated among inflammation, oxidative stress, and thyroid dysfunction …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And thyroid hormones can affect insulin signalling indirectly through affecting tyrosine phosphorylation of insulin receptor substrate and activation of phosphoinositide 3‐ kinase, serum FT3 levels are associated with insulin secretion . Furthermore, thyroid hormones and thyroid hormone receptors may play important roles in modulating the inflammatory response, and interactions have been demonstrated among inflammation, oxidative stress, and thyroid dysfunction …”
Section: Discussionmentioning
confidence: 99%
“…A recent cohort study by Shin et al showed that thyroid hormone replacement therapy not only preserved renal function, but was also an independent predictor of renal outcome in CKD patients with SCH. It had been reported that triiodothyronine restored renal phosphatidylinositide 3‐kinase activity and decreased renal transforming growth factor‐β1 expression in db/db mice, similar to the function of insulin . It is therefore important to screen and detect thyroid hormones changes in DN patients, especially those with SCH and/or low‐FT3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been reported that hypothyroidism induced by antithyroidal drugs can prevent pulmonary and cutaneous fibrosis induced by hypochlorous acid (51) and to improve survival after acute thioacetamide administration in the rat (52). However, hypothyroidism also induces cardiac fibrosis in the rat (53,54), thyroid hormone administration ameliorates kidney fibrosis (55), and thyroid disfunction and subclinical hypothyroidism have been associated with primary biliary cirrhosis, primary sclerosing cholangitis, and nonalcoholic fatty liver disease in humans (29,32). These observations reveal the complex role of the thyroid hormones on fibrosis that could depend on the type of insult or tissue examined.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model done in 2011 seemed promising. [23] 1236 Levothyroxine replacement was shown to preserve renal functions and independently predict renal outcome in 309 patients with stage 2-4 chronic kidney disease and SCH. [24] Another study showed that thyroid replacement therapy may slow down the deterioration of eGFR in a cohort of patients, 39% of which had diabetes mellitus.…”
Section: Discussion:-mentioning
confidence: 99%